2018
DOI: 10.22146/ijbiotech.32141
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic activity and apoptosis induction of avocado Persea americana Mill. seed extract on MCF-7 cancer cell line

Abstract: Avocado Persea Americana Mill. is a commercially important crop and studies have shown that the pulp may have benefits to cardiovascular health, dermatological health and possibly anti-cancer activity. Avocado seeds have several medicinal properties such as anti-hyperglycemic, antimicrobial, antioxidant and anti-inflammation. This study aim to evaluate the effect of avocado seed extract on viability and apoptosis of breast cancer cell line MCF-7. The anticancer effect was evaluated by cytotoxic test using MTT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
0
12
0
2
Order By: Relevance
“…The methanol fraction of chloroform extract of avocado seed was known to increase the population of MCF7 cells in the sub G1 phase by 21.9% compared to control cells (3.7%). These results indicate the induction of apoptosis in MCF7 cells (Widiastuti et al, 2018). Veles-Pardo et al (2014) reported that avocado peel extract, avocado seed extract, and avocado leaf extract could induce apoptosis in lymphoblastic leukaemia cells.…”
Section: Apoptosis Observation By Double Stainingmentioning
confidence: 79%
See 1 more Smart Citation
“…The methanol fraction of chloroform extract of avocado seed was known to increase the population of MCF7 cells in the sub G1 phase by 21.9% compared to control cells (3.7%). These results indicate the induction of apoptosis in MCF7 cells (Widiastuti et al, 2018). Veles-Pardo et al (2014) reported that avocado peel extract, avocado seed extract, and avocado leaf extract could induce apoptosis in lymphoblastic leukaemia cells.…”
Section: Apoptosis Observation By Double Stainingmentioning
confidence: 79%
“…The n-hexane fraction of avocado seeds at a concentration of 200 µg/mL inhibits 81±3% of lung cancer cells (A549) growth, while the dichloromethane fraction at the same concentration could inhibit the growth of gastric cancer cells (BGC823) of with inhibition rate of 75±2% (Vo et al, 2019). Chloroform extract of avocado seed was able to inhibit the growth of MCF7 cells with IC50 value of 94.87 µg/mL (Widiastuti et al, 2018). Alkhalaf et al (2019) showed that avocado seed extract inhibits the growth of liver cancer (HepG2) and colon cancer (HCT116) cells with lower IC50 values than avocado extract.…”
Section: Results and Discussion Cytotoxic Testmentioning
confidence: 99%
“…Concerning the cytotoxic activity of avocado seed extracts on cancer cells, Alkhalf et al [ 28 ] evaluated a lipid seed extract that exhibited anti-cancer activities in a concentration-dependent manner on the HCT116 (colon cancer) and the HePG2 (liver cancer) human cell lines. Likewise, chloroform extract from avocado seed showed strong cytotoxic activity against the MCF-7 cell line with an IC 50 = 94.87 μg/mL [ 29 ]. On the other hand, some non-steroidal anti-inflammatory drugs, such as carprofen and tolfenamic acid were cytotoxic for D-17 cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian lain juga menunjukkan aktivitas sitotoksik biji alpukat pada berbagai sel kanker. Ekstrak kloroform biji alpukat mampu menghambat pertumbuhan sel MCF7 dengan nilai IC50 94,87 µg/mL (Widiastuti et al, 2018). Fraksi n-heksan biji alpukat (200 µg/mL) dapat memberikan penghambatan sebesar 81±3 % pada pertumbuhan sel kanker paru-paru (A549) (Vo et al, 2019).…”
Section: Hasil Dan Pembahasanunclassified
“…Fraksi metanol ekstrak kloroform biji alpukat terbukti dapat meningkatkan (21,9%) populasi sel MCF7 yang berada pada fase sub G1 dibandingkan dengan kontrol sel (3,7%), hasil tersebut mengindikasikan terjadinya induksi apoptosis pada sel MCF7 (Widiastuti et al, 2018). Penelitian lain melaporkan bahwa ekstrak lipid buah alpukat dapat meningkatkan ekspresi caspase8 dan caspase 9 pada sel kanker kolon (Caco-2) (Lara-Márquez et al, 2020).…”
Section: Uji Penghambatan Proliferasi Selunclassified